Preventive Strategies for Ventilator Associated Pneumonia - J. Boots, Robert; Udy, Andrew; Holley, Anthony; Lipman, Jeffrey (Current Respiratory Medicine Reviews, 2010)
Ventilator associated pneumonia (VAP) increases mortality and hospital length of stay, In addition, increased costs can be directly linked to the development of VAP in the critically ill. Significant variability exists in the incidence of VAP, which is not entirely accounted for by the variation in case-mix between intensive care units. Controversy exists regarding the need for bronchoscopic or other invasive diagnostic techniques compared to clinically based diagnosis. VAP occurs as a result of airway colonisation with pathogenic bacteria, aspiration into the distal airways and the progression of tracheobronchitis to pneumonia. Preventive measures involve strategies to prevent aspiration, limit the duration of mechanical ventilation and reduce the potential for contamination by ventilation equipment. Pharmacological prophylaxis and infection control procedures aim to reduce airway bacterial colonization. The introduction of protocolised strategies to reduce VAP with performance monitoring has shown efficacy in reducing this complication of mechanical ventilation.
Keywords: acute respiratory distress syndrome